Regional model code of practice regarding HIV and AIDS for Caribbean medical practitioners - Aarons, Derrick (PANCAP Coordinating Unit GeorgetownGY, 2010)
Sets out a number of principles to be adopted in the Caribbean regional response to HIV infection.